THEORETICAL BASES OF DETERMINATION OF STANDARD FUNCTIONAL TYPES OF SECURITY OF AUTOMATIC SYSTEM FROM UNAUTHORIZED ACCESS - Юдін, О. К.; Бучик, С. С.; Мельник, С. В. (Science-based technologies, 2016)
The theoretical bases of determination of standard types of security of automatic system from the unauthorized access is shown, analysed and offered in the article. The necessary normative documents of technical security information, which regulate the order of estimation and determination of standard functional types of security of information from an unauthorized access in Ukraine, are reflected. On the basis of these documents, formalization of the bases of determination of standard types of security of automatic system from an unauthorized access is carried out for the first time. An example of determination of standard type of security is made after the presented formalized model. Theoretical bases offered by the authors enable in future to work out a consulting model which will determine the standard types of security of automatic system automated from an unauthorized access. It will facilitate the work of administrators of safety in relation to determination of type of security and creation of necessary complex of facilities of security, and also will decrease the spent resource of time.